Audit Domain Acquire And Implement dengan Cobit 4.1 pada PT Erajaya Swasembada Tbk - Viany Utami Tjhin (Bina Nusantara University, 2014)
The main priority aspect of information and communication technologies is given to control mechanisms, both internal and external in enterprises. It ensures that the reports and the decisions received and generated by the management will support their decision-making. The decisions have honesty and high integrity based on the results of the audit conducted on systems of information and communication technology. The objective of this research is to deliver audit reports of information systems for management and make recommendations on the audit findings in PT Erajaya Swasembada Tbk. Business processes studied included sales, purchasing, finance, and the warehouse. The system used was